Chemical-looping combustion of solid fuel in a 100 kW unit using sintered manganese ore as oxygen carrier. (October 2017) - Linderholm, C.; Schmitz, M.; Biermann, M.; Hanning, M.; Lyngfelt, A.
Highlights: Chemical-looping combustion (CLC) is a fluidized-bed technology with potential to drastically reduce the cost of CO2 capture. Using sintered manganese ore as oxygen carrier, high gas conversion (up to 88%) and very high carbon capture (almost 100%) was achieved. The size of the fuel particles had a crucial impact on performance. A rigorous investigation concerning the fate of nitrogen showed that the main product of fuel‑N is N2 . The expected lifetime of the oxygen carrier during fuel operation was found to be 100–400 h depending on the operating conditions. Abstract: Carbon capture and storage (CCS) offers the opportunity to avoid CO2 emissions from for example power plants and cement factories. Chemical-looping combustion (CLC) is one of the most promising capture technologies with potentially very low cost of CO2 capture. In this study we present findings from a solid-fuel 100 kW chemical-looping combustor. A new oxygen carrier – a sintered manganese ore called Sinaus – has been studied in the Chalmers 100 kW unit. The material has been investigated for an operational time of 51.5 h using five fuels: two bituminous coals, two types of wood char, and petcoke. The operational results clearly demonstrate the viability of the CLC process. In comparison to previously used iron-based oxygen carriers, the Sinaus material showed higher gas conversion – up to 88% – and lower loss of char to the air reactor, with carbon capture reaching as high as 100%. Furthermore, the solid-fuel conversion was higher, which is mainly an effect of the choice of fuel size. It was found that the choice of fuel has a crucial impact on performance. Previous experience has shown that the use of large fuel particles gives low carbon capture, whereas pulverized fuel leads to low solid-fuel conversion. By choosing the appropriate – intermediate – size of fuel, it is possible to combine high carbon capture with high solid-fuel conversion. Previous studies indicate that the drawback of many manganese ores is the mechanical stability. Hence, a lot of emphasis was put on an in-depth study of the lifetime of the Sinaus material. Analyzing the production rate of fines, it was found the expected lifetime of the Sinaus particles was 100–400 h. This is lower than what has been found for iron-based material, but most likely sufficient for operation in full-scale chemical-looping applications. Whilst the production of fines was highest during operation with fuel, a lot of fines were produced also during operation without fuel. Seven experiments without fuel, i.e when the observed mechanical degradation was only due to high-velocity impacts and not chemical stress caused by phase transformations, gave a lifetime in the interval 220–1230 h. In conclusion, this first-of-its-kind investigation shows that the lifetime of the oxygen carrier is related to both the change in oxygen-carrier conversion and high-velocity impacts.